MENGHADAPI REALITAS: APAKAH PERTUMBUHAN PENDUDUK MENJADI KATALISATOR ATAU ANCAMAN BAGI PEMBANGUNAN EKONOMI YANG BERKELANJUTAN DI NEGARA BERKEMBANG? - Ananda Nayla Rahma Esafitri; Wahiddin Choiri Kurniawan; Heni Noviarita (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2025)
Population growth in developing countries is an inevitable reality that continues to rise over time. This phenomenon presents both challenges and opportunities in planning for sustainable economic development. On one hand, an increasing population can drive economic growth by expanding markets and providing a labor force that supports productivity and innovation. On the other hand, rapid population growth may place significant pressure on natural resources, infrastructure, and public services. This can hinder economic progress and exacerbate social inequality. This study highlights the importance of strategic policies in managing population growth to ensure it becomes a positive force for inclusive and sustainable development.